A colorimetric bioassay for quantitation of both basal and insulin-induced glucose consumption in 3T3-L1 adipose cells (2020)
Introduction: The quantitation of glucose consumption in animal cell cultures is mainly based on the use of radiolabeled or fluorescent analogues, resulting in expensive and tedious procedures, requiring special equipment and, sometimes, with potential health and environmental risks. Objectives: The objective of this work was to evaluate the application of a blood plasma colorimetric assay to quantify glucose consumption in in vitro cultures of adipose cells. Methods: We worked with 3T3-L1 adipose cells differentiated by 7–8 days, which were exposed to different initial glucose concentrations (5.5, 2.8 and 1.4 mM) for variable times, either in the absence or the presence of 100 nM insulin. Using a commercial colorimetric glucose assay, extracellular glucose was determined, and glucose uptake was calculated as the difference between the initial and final glucose concentration. Results: The colorimetric assay allowed us to quantify glucose uptake in our cell model, observing a linear response over time (r2?0.9303) to the different glucose concentrations, both in the basal and insulin-induced condition. The insulin-stimulated glucose consumption was higher than basal consumption at all glucose concentrations evaluated, but significant differences were observed at 120-, 360- and 480-min in glucose 5.5 mM (p ? 0.01, n = 5), and 240 min in glucose 1.4 mM (p ? 0.01, n = 5). A Vmax of 4.1 and 5.9 nmol/ml/min (basal and insulin-induced, respectively) and a Km of 1.1 mM (same in basal vs insulin-stimulated) were calculated. The bioassay was also useful in a pharmacological context: in glucose 1.4 mM, glucose consumption showed an effect that depended on insulin concentration, with a calculated EC50 of 18.4 ± 1.1 nM. Conclusions: A simple and low-cost bioassay is proposed to quantify glucose consumption in 3T3-L1 adipose cells. Biological Sciences; Cell biology; Cell Culture; Cell Differentiation; Metabolism; Biological Assay; bioassay; In Vitro Techniques; Adipocytes; 3T3-L1 Cells; Glucose consumption; Glucose uptake; Insulin; Insulin action; Insulin response. © 2020 The Authors